Total Organic Carbon Analysis of Residual Contaminants in Bioreactor Equipment: A Cleaning Verification Study using Surface Swabbing - Ciara E. Fitzpatrick; James J. Roche (SURE Journal: (Science Undergraduate Research Experience Journal))
Contamination is a major issue in the biopharmaceutical industry. Bioreactors must be meticulously cleaned to remove residual impurities and avoid cross-contamination. Cleaning validation is necessary to ensure residual contaminants are reduced to the lowest acceptable limits. Bacterial cells represent the paramount challenge in manufacturing equipment cleaning because they are composed of insoluble organic contaminants. Total organic carbon (TOC) analysis is a fast, highly sensitive, and inexpensive analytical technique commonly used to evaluate the approximate level of organic contamination. A study was conducted to assess the effectiveness of cleaning procedures in the removal of contaminants from bioreactor equipment by measuring the TOC concentration of swab samples. A bioreactor was used to obtain a high-density culture of Escherichia coli JM109 cells and a popular enzyme-active anionic detergent was chosen to clean the equipment surfaces. The areas selected for swab sampling included the borosilicate glass vessel and stainless steel impeller blades. The TOC analyzer was calibrated using purified water (blank) and a series of sucrose standard solutions in the range of 1.0 to 100 mg/L. The correlation coefficient (r) was determined to be 0.99911. The limit of detection and limit of quantitation were determined to be 3.46 and 12.89 mg/L, respectively. These results demonstrated that the TOC analyzer was suitable for its intended use. The acceptance limit for the cleaning verification study was calculated to be 7 μg residual matter per cm2 based on a 1 L batch size and a total contact surface area of 1489 cm2. The TOC values obtained for each of the sampled surfaces were significantly above this threshold. Strikingly, the stainless steel blades were found to have the highest levels of contamination with a value of 295 μg/cm2. The high levels of organic contamination were attributed to the enzyme-active anionic detergent that was used during the cleaning procedure. Despite the widespread use of this detergent in the biopharmaceutical industry, there are limited reports describing its use in cleaning validation studies. These findings suggest that this area of research warrants further investigation to ensure that the use of such detergent in bioreactor equipment cleaning does not negatively affect the safety and quality of the subsequent manufactured product. To conclude, the results of this study highlight the importance of cleaning verification, small-scale experimentation, and detergent selection.